Political Communication Strategy "Nyantri" in the 2024 Regional Election Campaign in Rembang Regency from the Perspective of Dramaturgy Theory - Qodrun Nada, Dewi; Addiansyah, Mohammad Nur Rofiq (Journal of Social and Policy Issues, 2025)
This study aims to explain and provide a comprehensive overview of the strategies employed by the two candidate pairs for Regent and Deputy Regent in the 2024 Pilkada campaign in Rembang Regency, using Erving Goffman’s Dramaturgy Theory approach. This research adopts a qualitative method, utilizing both primary and secondary data sources.  Primary data were collected through observations of five posts on the Instagram accounts of both candidates. The author observed these accounts over two months, from the beginning of the campaign period on Wednesday, September 25, 2024, to Saturday, November 23, 2024. Secondary data were gathered through literature studies, including journal articles, e-proceedings, and books, which served as additional sources. The collected data were then analyzed using the Dramaturgy Theory framework.  The analysis reveals that both candidate pairs actively construct their public image on social media, particularly on Instagram. Their primary objective is to highlight their religious identity to gain public sympathy in Rembang Regency. Their campaign strategy involves engaging with local Kiai and Ulama—positions they adopt as Santri within the Dramaturgy framework—and showcasing these interactions on Instagram, a key political communication platform. This approach aims to strengthen their positive reputation in a predominantly religious society, thereby enhancing their public image among the people of Rembang Regency.